Optimizing Employee Communication in Organizational Behavior with Collaborative Methods at PT. Resonac Materials Indonesia - Riswandi; Waode Kharisma; Tantri Kusumastuti; Geofakta Razali (Formosa Journal of Sustainable Research, 2023)
Improved employee performance has a good impact on realizing company value. Everyone has personal interests that may not be in line with the vision and mission. This results in a communication gap between employees and management level. If a communication gap occurs, the company's goal to achieve the target will be hampered. The importance of increasing the intensity of communication between employees with the Collaboration method applied at PT Resonac Materials Indonesia. The theory that underlies this research method includes dyadic power theory. From the results of socialization and discussion, 4 responses emerged. This breakthrough is applied to focus on employees. Employees cannot work alone. Cooperation is needed and optimal collaboration will produce new ideas to create future interactions with new expectations